Influence of polyethylene glycol coating on biodistribution and toxicity of nanoscale graphene oxide in mice after intravenous injection - Li B (Dove Medical Press, 2014)
Bo Li,1,2 Xiao-Yong Zhang,1 Jian-Zhong Yang,1 Yu-Jie Zhang,1 Wen-Xin Li,1 Chun-Hai Fan,1 Qing Huang1 1Laboratory of Physical Biology, Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai, 2Department of Human Anatomy, College of Basic Medical Sciences, Jilin University, Changchun, People’s Republic of China Abstract: In this study, we assessed the in vivo behavior and toxicology of nanoscale graphene oxide (NGO) in mice after intravenous injection. The influence of a polyethylene glycol (PEG) coating on the distribution and toxicity of the NGO was also investigated. The results show that NGO is mainly retained in the liver, lung, and spleen. Retention in the lung is partially due to NGO aggregation. The PEG coating reduces the retention of NGO in the liver, lung, and spleen and promotes the clearance of NGO from these organs, but NGO and NGO-PEG are still present after 3 months. The PEG coating effectively reduces the early weight loss caused by NGO and alleviates NGO-induced acute tissue injuries, which can include damage to the liver, lung, and kidney, and chronic hepatic and lung fibrosis. Keywords: graphene oxide, biodistribution, toxicity, polyethylene glycol